2020
DOI: 10.1073/pnas.1918649117
|View full text |Cite|
|
Sign up to set email alerts
|

Arrhythmogenic late Ca 2+ sparks in failing heart cells and their control by action potential configuration

Abstract: Sudden death in heart failure patients is a major clinical problem worldwide, but it is unclear how arrhythmogenic early afterdepolarizations (EADs) are triggered in failing heart cells. To examine EAD initiation, high-sensitivity intracellular Ca2+ measurements were combined with action potential voltage clamp techniques in a physiologically relevant heart failure model. In failing cells, the loss of Ca2+ release synchrony at the start of the action potential leads to an increase in number of microscopic intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 46 publications
(56 reference statements)
3
31
0
Order By: Relevance
“…Such results support the idea that modulation of I to,f could be beneficial in heart failure [4]. We recently showed that electrophysiological restoration of phase 1 of the AP can improve SR release synchrony, suppress arrhythmogenic late Ca 2+ spark production and increase the amplitude of the Ca 2+ transient in a heart failure model [16] in agreement with the earlier demonstration that the loss of human phase 1 repolarization impairs excitation-contraction coupling (ECC) [14]. However, increasing I to,f pharmacologically (with the I to agonist NS5806) in a dog ventricular wedge preparation led to the emergence of Brugada-like electrical abnormalities [17] while in intact rabbit heart, NS5806 also promoted arrhythmias (although Brugada-like behaviour did not necessarily appear) and was suggested to be the consequence of defective Ca 2+ cycling [18].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Such results support the idea that modulation of I to,f could be beneficial in heart failure [4]. We recently showed that electrophysiological restoration of phase 1 of the AP can improve SR release synchrony, suppress arrhythmogenic late Ca 2+ spark production and increase the amplitude of the Ca 2+ transient in a heart failure model [16] in agreement with the earlier demonstration that the loss of human phase 1 repolarization impairs excitation-contraction coupling (ECC) [14]. However, increasing I to,f pharmacologically (with the I to agonist NS5806) in a dog ventricular wedge preparation led to the emergence of Brugada-like electrical abnormalities [17] while in intact rabbit heart, NS5806 also promoted arrhythmias (although Brugada-like behaviour did not necessarily appear) and was suggested to be the consequence of defective Ca 2+ cycling [18].…”
Section: Introductionsupporting
confidence: 78%
“…Computer simulations have also shown an abrupt reduction in AP duration at ~0.13 nS/pF (corresponding to ~14 pA/pF) [ 57 ] in agreement with our results. While such an AP collapse might recapitulate Brugada syndrome [ 17 ], our data shows that controlled Kv4.3/KChIP2.1 expression and restoration of I to,f could be beneficial in reducing AP triangulation and beat-to-beat variability (the latter probably reflecting a more synchronous Ca 2+ release [ 16 , 58 ]). That modulating these key components of I to,f might reduce the risk of arrhythmia is also supported by the observation that increasing KChIP2 expression (or inhibiting miR-34) under pathologic conditions prevented reentry arrhythmias [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the role of Ca 2+ in the generation of DADs, 4 6 , 21 , 35 subsequent experiments were designed to determine whether the antiarrhythmic effects of sildenafil were mediated by changes in intracellular Ca 2+ cycling. Cellular calcium waves were induced in voltage-clamped left ventricular myocytes by raising the external Ca 2+ concentration to 10 to 15 mmol/L to increase SR Ca 2+ content (control, 44.3±12.6 µmol/L; high Ca 2+ , 104.4±14.6 µmol/L; P =0.004; Figure IV in the Data Supplement ).…”
Section: Resultsmentioning
confidence: 99%
“…2). The effects of dantrolene on APD (and EAD formation) might be explained by the attenuation of SR Ca 2+ leak-induced CaMKII activity, changes in myocyte Na + and Ca 2+ loading, enhanced inward NCX, and late Ca 2+ sparks, which can activate the vicious cycle and influence AP configuration [14]. Dantrolene also markedly attenuated APD prolongation, alternans, and spontaneous diastolic activities (i.e., DADs, sAPs) in hiPSC-CMs carrying SCN5A N406K mutation, highlighting the critical role of SR Ca 2+ leak (and the activated vicious cycle) in these arrhythmias (Fig.…”
Section: Discussionmentioning
confidence: 99%